The Influence Of Work Environment And Skills On Agricultural And Fisheries Food Security Employees' Performance In Bekasi City - Tussoleha Rony, Zahara; Christina Siboro , Maria (International Publisher, 2023)
This study aims to determine the influence of the work environment and work skills on the performance of employees of the Food Security, Agriculture, and Fisheries Office of Bekasi City. The data analysis method used is quantitative. The sample for this research was 70 respondents who were employees of the Department of Food Security, Agriculture, and Fisheries, Bekasi City. Data collection was carried out using a questionnaire that had been tested for validity and reliability. Data processing using SPSS Version 26 Data analysis techniques using multiple linear regression analysis The results of this study indicate that the work environment variable and the work skills variable have a positive and significant impact on employee performance. and simultaneously, these two independent variables are proven to be significant and have an effect on employee performance variables.